(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Agricultural modernization allows to ensure efficiency and increase the competitiveness of agricultural producers and enterprises. Therefore, in the Action Strategy for five priority areas of development of the Republic of Uzbekistan for 2017-2021, it is noted that the implementation of investment projects for the construction of new, reconstruction and modernization of existing processing enterprises equipped with the most modern high-tech equipment for deeper processing of agricultural products, the production of semi-finished products and finished food products, as well as packaging products is one of the priority areas of modernization and intensive development of agriculture.The article identifies topical problems associated with the modernization of agriculture and developed scientific proposals aimed at solving these problems.